Antibacterial properties of copper-tantalum thin films: The impact of copper content and thermal treatment on implant coatings - Bagdat Azamatov; Alexey Dzhes; Alexander Borisov; Daniyar Kaliyev; Bauyrzhan Maratuly; Amangeldi Sagidugumar; Myakinin Alexandr; Amanzhol Turlybekuly; Sergei Plotnikov (Heliyon)
This study evaluates the antibacterial properties and physicochemical characteristics of –tantalum-copper (Ta-Cu) coatings deposited on titanium alloy substrates using high-power magnetron sputtering. Implant-associated infections, particularly those caused by bacterial adhesion and biofilm formation, pose significant challenges in the field of orthopedic and dental implants. To address these issues, Ta-Cu coatings with varying copper content (∼3.0 wt%, ∼10 wt%, ∼17 wt% for TaCu-1, TaCu-2, and TaCu-3, respectively) and different thermal treatment conditions (400 °C, 500 °C, 600 °C) were assessed for their antibacterial efficacy against Escherichia coli, Staphylococcus aureus, Salmonella enterica, and Pseudomonas aeruginosa. The study utilized both the diffusion into agar method and the time-kill test to evaluate antibacterial activity. Results indicate that the TaCu-2 sample, particularly when annealed at 600 °C, demonstrated the highest bactericidal activity, especially against E. coli and P. aeruginosa. The findings highlight the critical role of optimizing both copper content and annealing temperature in enhancing the antibacterial properties of Cu-Ta coatings, making them promising candidates for preventing implant-associated infections.